THE BODY IN THE CONTEMPORARINESS AND THE ROLE OF PHYSICAL EDUCIATION WITHIN THIS CONTEXT . (Fiep Bulletin - online, 2012)
The present interpretative article presents a reflection upon the role of Physical Education within the body context inthe present days. We can notice a change in how the body has been seen and manifested throughout time. Today, we observethat the body has been acting as a stage for an unbridled pursuit of beauty, following an ideal standard imposed by the media.Given the stereotype built within this reality, it is of paramount importance that the Physical Education professionalsimpose a critical look upon such condition. They must have in mind that such given standard not always respect the individuallimitations. Thus, they shall act as mediators, acting critically when performing their job. It is critical to observe the limitations andspecifications of each individual in society, and how far it would be healthy to follow this unbridled pursuit of the archetypepresented by the various media we have today. Therefore, our study aims to emphasize how the physical education professionalshall act within such context, having a critical look upon its practice and not acting as a mere reproducer of what is being imposed.
Keywords: body; contemporaneity; physical education.